2011
DOI: 10.2105/ajph.2010.191676
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tobacco Outlet Density and Proximity on Smoking Cessation

Abstract: Because residential proximity to tobacco outlets influences smoking cessation, zoning restrictions to limit tobacco sales in residential areas may complement existing efforts to reduce tobacco use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
129
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 23 publications
9
129
0
Order By: Relevance
“…[27][28][29] However, the lower quit rates and the additional barriers described by pregnant women with mental disorders are consistent with research on people with mental disorders outside pregnancy; this may be because they are more heavily addicted. 30 In addition, health professionals have not traditionally prioritised smoking cessation in people with mental disorders, possibly because of beliefs that people with mental disorders are less likely to want to stop smoking or that it will worsen the disorder.…”
Section: Main Findingssupporting
confidence: 69%
“…[27][28][29] However, the lower quit rates and the additional barriers described by pregnant women with mental disorders are consistent with research on people with mental disorders outside pregnancy; this may be because they are more heavily addicted. 30 In addition, health professionals have not traditionally prioritised smoking cessation in people with mental disorders, possibly because of beliefs that people with mental disorders are less likely to want to stop smoking or that it will worsen the disorder.…”
Section: Main Findingssupporting
confidence: 69%
“…This study observed an association between quit success and proximity of the quitter's home to a tobacco retailer, but not with retailer density. 31 Further research on the influence of retailer density around homes and workplaces on relapse is needed.…”
Section: Discussionmentioning
confidence: 99%
“…8 Recent years have seen a growing interest in reducing tobacco availability via retail outlets, 9 along with growing evidence that the distribution of outlets may impact tobacco use behavior. Studies have found that outlet density is associated with increased cigarette smoking among youth, [10][11][12][13][14] while outlet proximity [15][16][17][18] is associated with reduced smoking cessation among adults. However, evidence examining the impact of outlets on cigarette smoking or use of other tobacco products among young adults is scarce.…”
Section: Original Investigationmentioning
confidence: 99%